John Joseph Craven papers - Craven, John Joseph, 1822-1893.; Craven, Catherine S.; Craven, William Darcy, 1846-
Correspondence, diary, family papers, legal records, patent, photographs, and other papers. Includes Craven's letters to his wife, Catherine S. Craven, from aboard ship and from California during the Gold Rush; fragments of a diary written at Fort Monroe concerning Craven's medical treatment of Jefferson Davis; text of a court trial (1874-1875) involving Craven's invention of a submarine telegraph cable; and a British patent (1876) for a refrigerator. Family papers include his wife's diary (1863) and papers of their son, William Darcy Craven.
Inventor, physician, and U.S. Army officer.
Collection material in English.
Keywords: Davis, Jefferson, -- 1808-1889.; Craven family; Cables, Submarine; Refrigerators -- Patents; Telegraph cables; California -- Gold discoveries; Fort Monroe (Va.) -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Medical care; Army officers; Inventors; Physicians